Neighborhood Prime Labeling in Some Product And Power Digraphs. Issue 1 (June 2021) - Palani, K; Shunmugapriya, A; Meenakumari, N
Abstract: Let D ( p, q ) be a digraph. A function f : V → 1, 2, …, n is said to a neighborhood prime labeling of D if it is both in and out degree neighborhood prime labeling. In this paper, we introduce the concept of neighborhood prime labeling in digraphs and also investigate the existence of neighborhood prime labeling in some digraphs.